Institutional Arrangements for Public Debt Management - Currie, Elizabeth; Dethier, Jean-Jacques; Togo, Eriko (World Bank, Washington, DC, 2014)
This paper analyzes institutional arrangements for public debt management by reviewing the experience of OECD countries during the late 1980s and 1990s. It discusses principal-agent issues arising from the delegation of authority from the Minister of Finance to the debt management office and describes how countries have designed governance structures and control and monitoring mechanisms to deal with these issues. The paper also discusses what lessons emerging market countries and transition countries can draw from the experience of advanced OECD countries. The OECD experience clearly indicates that-regardless of whether the debt management office is located inside or outside the Ministry of Finance-four issues are of vital importance: 1) Giving priority to strategic public policy objectives rather than tactical trading objectives. 2) Strengthening the institutional capacity to deal with financial portfolio management and with the public policy aspects of debt management. 3) Modernizing debt management. 4) Creating mechanisms to ensure successful delegation and accountability to the Ministry of Finance and Parliament.